CHARACTERISTICS OF BOTTOM TOPOGRAPHY AND SEABED SEDIMENTS IN WATER OF THO CHU ISLANDS - Trung, Pham Ba (Vietnam Journal of Marine Science and Technology, 2016)
Tho Chu archipelago was formed by sedimentary rocks (176 metres in height) with horizontal position. The islands are limited by the abraded slopes and landslide disruption. The shoreline morphology is cliffs, abrasion and boulders with good size, low abrasion, and little change. Vegetation of island is still in the primary condition. The average depth of Tho Chu archipelago is about 20 - 30 m with canyons of -96 m and several underwater hills which are covered by coral reefs. The characteristics of seabed sediment are mostly kinds of coarse - grained sediments such as gravelly sand (gS), slightly gravelly muddy sand ((g)mS), muddy sand (mS), mud (M).